THE INFLUENCE OF PERCEIVED USEFULNESS, EASE OF USE, COMPATIBILITY AND RISK ON MOBILE BANKING USER ATTITUDE (Study at PT. Bank Rakyat Indonesia Tbk. Branch Malang Kawi) - Restu Andhi Ardana (Jurnal Administrasi Bisnis, 2014)
This  research  has the background to know  implementation  use of Mobile Banking in PT Bank Rakyat Indonesia.  The purpose of this research is to know  how the influence of Perceived Usefulness, Ease of Use, Compatibility, and Risk On Mobile Banking User Attitude PT Bank Rakyat Indonesia Malang Kawi. Type of this research can be considered as  explanatory research with the hypothesis testing  and  this study  is  using accidental sampling technique where the  use  criteria are  all customers  that using  mobile banking facility that amount 96 person. The  result can be seen that positive  effect  between  usefulness, ease of use, compatibility,  risk  variables  on  mobile banking user attitude  it can be  seen the  F  equal to 22.028  with a  Fsignificance  equal to 0.000  (p<0.05).  There are  usefulness  variable  who  has a  influence  dominant,  proved with  has highest  coefficient  beta  0,291  and  t  2,987  as well as  value of  probability  0,004  (p<0,05).  While known  amount of  the effect  of  four variables  simultaneously  on  mobile banking user attitudes  as seen fromadjusted R square value 0,470 the value indicates that each variable contributed respectively 47% to mobile banking user attitude. While 53% were influenced by other variables not examined in this study.Keywords: Usefulness, Ease of Use, Compatibility, Risk, User AttitudeAbstrakPenelitian ini mempunyai latar belakang untuk mengetahui bagaimana implementasi penggunaan Mobile Banking di PT Bank Rakyat Indonesia. Tujuan dari penelitian ini untuk mengetahui bagaimana pengaruh Persepsi Kegunaan, Kemudahan Penggunaan, Kesesuaian, dan Risiko Pada Sikap Pengguna Mobile Banking studi di PT Bank Rakyat Indonesia Cabang Malang Kawi. Jenis penelitian ini adalah penelitian penjelasan dengan pengujian hipotesis dan metode pengumpulan sampel dalam penelitian ini menggunakan teknik accidental sampling dimana kriteria penggunaan semua nasabah yang menggunakan fasilitas mobile banking yang berjumlah 96 orang. Dari hasil penelitian dapat diketahui bahwa pengaruh positif antara kegunaan, kemudahan penggunaan, kesesuaian, dan risiko berpengaruh pada sikap pengguna mobile banking dapat dilihat dari nilai F 22,028 dengan signifikansi F sebesar 0,000 (p<0,05), Selain itu, variabel kegunaan yang memiliki pengaruh paling dominan, terbukti dengan memiliki koefisien beta tertinggi yaitu 0,291 dan t 2,987 serta nilai probabilitas 0,004 (p<0,05). Sementara diketahui jumlah pengaruh dari empat variabel secara simultan ke sikap pengguna mobile banking seperti yang terlihat dari Adjusted R Square dengan nilai 0,470 menunjukkan bahwa tiap variabel memberikan kontribusi masing-masing sebesar 47% terhadap sikap pengguna mobile banking. Sementara 53% dipengaruhi oleh variabel lain yang tidak diteliti dalam penelitian ini. Kata kunci : Kegunaan, Kemudahan Penggunaan, Kesesuaian, Risiko, Sikap Pengguna